Peptidomimetics Protocols - Kazmierski, Wieslaw M.; Kazmierski, Wieslaw M. (Methods in Molecular Medicine,, 1999)
In Peptidomimetics Protocols, Wieslaw Kazmierski assembles a state-of-the-art collection of detailed synthetic procedures that lead to a variety of scaffolds, turn mimetics, peptide-bond replacements, and enzyme inhibitors. Topics range from syntheses of unusual amino acids, to the use of a variety of linear and heterocyclic scaffolds in place of the peptide backbone. Important chemical procedures and methods include the transient protection of charged peptides as neutral prodrugs for improved blood-brain penetration and the replacement of otherwise labile peptide bonds with heterocyclic rings, olefins and fluoroolefins, and ketomethylenes. Synthetic protocols towards the transition-state mimics and reactive "warheads," applicable in enzyme inhibitors, are also disclosed. Peptidomimetics Protocols is the first book devoted to the practical synthetic preparation of peptide mimetics. Written by both academic and industrial synthetic organic and medicinal chemists, this book provides highly practical synthetic procedures for the generation of key peptide mimetics, and so immediately becomes a must-have desk reference and guide for all medicinal and pharmaceutical chemists engaged in the discovery and development of pharmaceuticals today.